A theoretical overview of road hump effects on traffic speed in improving residential living environment - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (2015)
This paper is part of ongoing study to analyse the effectiveness of road humps as a traffic calming measure in improving the residential living environment. Concerns have been raised that high traffic speeds impact neighborhood liveability; therefore in order to discuss the effectiveness of road humps in improving the Malaysian residential living environment, a review has been conducted on various literatures concerning the effects of road humps on vehicle speeds. Some of the major findings from the literatures are that the vehicle's operating speed is affected by the spacing in between a series of humps, though the recommended speed differs in various literatures. An incorrect hump profile will also decrease the hump's effectiveness and potentially result in passenger discomfort and vehicle damage. In addition, the road hump design is the key point in hump's effectiveness in reducing 85th percentile vehicle speeds; however, care must be taken in ensuring that the hump profile does not only cater for reduction in speeds, but also addresses the numerous concerns resulting in reduced manoeuvrability for buses and emergency vehicles. More research needs to be carried out to test the effectiveness of current schemes in Malaysian residential areas as the existing installations are mainly on an ad-hoc basis.